Kritik Sosial Lirik Lagu ”Feast” - Rizkya Azzahra; Merliana Octavianie Irawan (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
Song lyrics "Civilization", "News of Loss", and "Great Destroyer Dance" works. Feast became the subject of this investigation. The purpose of this study was to provide an overview of the structure of lyrics and social commentary. The Roman Ingarden hypothesis is used in this review to dissect the design of the verses of the dining experience. Theories of literary sociology were also used in this study to see how the lyrics of the song "Pesta" contained social criticism. The consequences of this study show that melodic verses work . Banquet acts as a vehicle for delivering analysis of real social factors that occur in the eyes of the public. In the melodic poems of "Peradaban", analysis is communicated on the development of the revolution, the unfair worldview, and prejudice that exists among the tight networks that are rife in Indonesia. The killers were criticized in the lyrics of the song "News of the Loss" because it has lost humanity and human values. The lyrics of the song "Dance of the Great Destroyer" forbid the application of Indonesian local wisdom and denounce pollution and environmental damage.